Three case reports of eosinophilic gastroenteritis with milk, wheat, and peanut food allergy (Indian Journal of Case Reports, 2020)
Eosinophilic gastroenteritis (EGE) is an uncommon disease that can affect one or more organs of the digestive tract. EGE has a very low incidence rate and its diagnosis is challenging for any clinician. We report a case series of three cases of EGE who were evaluated for non-specific gastrointestinal symptoms and presented with an increase in eosinophils and total immunoglobulin E. The diagnosis of EGE was confirmed by histopathological findings. The causative food allergens were identified by provocation and elimination tests. The relevance of our case series lies in concomitant food allergy with the atopic constitution and the improvement of symptoms after the elimination of specific food is the mainstay for the management of EGE.